Analisis Risiko Keselamatan Kesehatan Kerja (K3) Karyawan dengan Metode Hirarc di UD. Fuad Las Jaya - Moh. David Syarifudin; Silvi Rushanti; Afiff Yudha Tripariyanto (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Each workplace has a different potential risk of work accidents depending on the type of industry, technology used, and risk control efforts undertaken by the company. Work accidents are generally caused by two main factors: unsafe acts by humans and unsafe working conditions. In this context, occupational safety and health (K3) is an important aspect that must be implemented in every company to protect workers from hazards that can cause losses, both physical and work productivity. Law No. 13 of 2003 concerning Manpower mandates that every worker has the right to occupational safety protection. This study focuses on UD. Fuad Las Jaya, a company engaged in construction and welding services. This company has a fairly high potential for work accidents considering the type of work performed. Based on employee attendance data in 2025, there is a level of discipline that can be related to working conditions and perceived safety. The severity of accidents is classified into three categories: light, moderate, and severe, which indicates the importance of implementing an effective K3 system. It is hoped that consistent awareness and implementation of K3 will create a safe, healthy, and productive work environment, as well as reduce the number of work accidents in the construction sector.